Genetic basis of Sjögren's syndrome. How strong is the evidence? (2006)
Sjögren's syndrome (SS) is a late-onset chronic autoimmune disease (AID) affecting the exocrine glands, mainly the salivary and lachrymal. Genetic studies on twins with primary SS have not been performed, and only a few case reports describing twins have been published. The prevalence of primary SS in siblings has been estimated to be 0.09% while the reported general prevalence of the disease is approximately 0.1%. The observed aggregation of AIDs in families of patients with primary SS is nevertheless supportive for a genetic component in its etiology. In the absence of chromosomal regions identified by linkage studies, research has focused on candidate gene approaches (by biological plausibility) rather than on positional approaches. Ancestral haplotype 8.1 as well as TNF, IL10 and SSA1 loci have been consistently associated with the disease although they are not specific for SS. In this review, the genetic component of SS is discussed on the basis of three known observations: (a) age at onset and sex-dependent presentation, (b) familial clustering of the disease, and (c) dissection of the genetic component. Since there is no strong evidence for a specific genetic component in SS, a large international and collaborative study would be suitable to assess the genetics of this disorder.